Pengaruh Indeks Pembangunan Manusia (IPM) dan Pertumbuhan Ekonomi terhadap Pengangguran dan Jumlah Penduduk Miskin di Samarinda - Cony Ayu Nurlita; Adnan Haris Musa; Rahcmad Budi Suharto (Jurnal Ilmu Ekonomi Mulawarman (JIEM), 2017)
The purpose of this research is to analyze the influence of the variable Human Development Index (HDI) and the growth of economy towards unemployment and the number of poor population in Samarinda. The implemented variable in this research is exogenous variable (x) which is human development Index (HDI) and the growth of economy, (y) which is unemployment and the numbers of poor population. In this research, kind of data used is secoundary data of by 2005-2014. The analysis instrument used is in the shape of 2 step structures which is analyzed using SPSS software (Statistical Package for Service Solution) versi 20. The result of this research showed that human development index (HDI) was not significantly towards influenced towards unemployment, the growth of economy has significantly influenced and has negative value towards unemployment, the human development index (HDI) has significantly influenced and has negative value towards the numbers of poor population, the growth of economy has not significantly influenced towards the numbers of poor population in Samarinda. The human development index (HDI) inderectly through unemployment pour population has significantly influence and has negative value towards the numbers of the growth of economy inderectly through unemployment  has not influenced toward the numbers of poor population in Samarinda.Keywords: Human Development Index (HDI)